Exploring the Effect of Anchor Characteristics on impulse buying among Generation Z in live streaming on short-form video apps - Jing, Siow Xiu; Phang, Ing Grace (International Journal of Accounting, Finance and Business, 2024)
Social commerce and live streaming shopping, particularly through social media channels and short-form video apps (e.g., TikTok), have gained substantial popularity among Generation Z. In the context of live streaming, anchor—individuals who present and promote products—play a pivotal role in influencing consumer behaviours. Despite their importance, the specific characteristics of anchor that influence Generation Z’s impulsive buying intentions in live streaming on short-form video apps remain unexplored. This study, utilizing the Stimulus-Organism-Response (S-O-R) model, aims to address this gap by examining the impact of anchor characteristics—namely attractiveness, expertise, and trustworthiness—on Generation Z’s impulsive buying intentions. A purposive sampling method was used to collect data from 272 Malaysian Generation Z individuals who have experience with live streaming shopping on short-form video apps. The analysis reveals that the attractiveness, expertise, and trustworthiness of anchor significantly affect consumer arousal and their intention to make impulsive purchases. This study is valuable to scholars and marketers as it provides insights into the attributes that make anchor effective in engaging Generation Z audiences, helping to refine marketing strategies and optimize live streaming practices.